The Impact of the Group Investigation (GI) Learning Model on Enhancing Middle School Students’ Science Literacy in Thermal Expansion Topics - Listiawan, Listiawan; Winarto, Winarto; Wiyatmo, Yusman (Jurnal Pendidikan MIPA, 2024)
Scientific literacy is essential skills that students must master in the 21st century. This study aims to examine the effect of the Group Investigation (GI) learning model on improving science literacy in Middle School students on thermal expansion. The research uses a pre-experimental method with a one-group pretest-posttest design. The sample consisted of one class selected through purposive sampling, namely class VII I at SMP Negeri 5 Yogyakarta. The data collection method involved using a test with a science literacy test in the form of multiple-choice questions. Data analysis was conducted using statistical tests to determine the differences before and after implementing the GI learning model. The study results indicate that the Group Investigation (GI) learning model can improve students' science literacy on thermal expansion. The enhancement in science literacy scores for indicators such as explaining phenomena scientifically, evaluating and designing scientific investigations, and interpreting data and evidence scientifically showed increases of 35.1%, 40.02%, 22.08%, and 39.98%, respectively. The paired sample T-test results indicated that the GI learning model significantly affected science literacy and its indicators. The N-gain test results showed that the GI learning model positively affected science literacy, with the indicators achieving scores of 0.42, 0.64, 0.39, and 0.29, categorized as moderate, moderate, moderate, and low, respectively. The calculated Cohen's d value of 1.457024 falls within the huge category based on Sawilowsky's (2009) criteria. This study concludes that implementing the GI learning model can improve students' science literacy on thermal expansion.      Keywords: group investigation, science literacy, thermal expansion, middle school. DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1549-1558